Da’wa in National Context: Da’wa for a Modern and Peaceful Indonesia - Syam, Nur (Proceedings of International Conference on Da'wa and Communication, 2020)
The Indonesian nation chooses moderate Islam as the choice in understanding and practicing religion. The choice of moderate Islam is the right choice considering that Indonesia is a pluralistic and multicultural country. By making moderate Islam as a choice in religion, it will provide enormous opportunities for the creation of a harmonious, harmonious, and safe society. Therefore, the preaching of Islam must also be appropriate in the corridor of da’wa that develops peace and safety. The propagators of Islam (da'i) certainly have to develop their da’wa by using an approach based on the desire to create a society based on Islam, Indonesian, and modernity. If the da'i can do it, it will be certain that in welcoming Golden Indonesia, in 2045, Indonesia will become a country that can be used as an example as a country with a high Islamic civilization.